Co-existing species of Drapetis Meigen in Skåne (S Sweden) with description of a new species and a key to males of NW European species (Diptera: Hybotidae) - Michelsen, Verner; Grootaert, Patrick (Zootaxa, 2019)
Drapetis is a genus of tiny predaceous hybotid flies found frequently on the bark of trees. From a single locality in province Skåne (S Sweden) we report the co-existence of seven species of Drapetis. One is new and described as D. abrollensis sp. nov., and four species, D. assimilis (Fallén), D. completa Kovalev, D. infitialis Collin and D. stackelbergi Kovalev, are relatively recent additions to the list of Swedish Diptera. A key to males of the 14 species of Drapetis known from NW Europe is given. Special emphasis is given to modifications of the midleg cuticle observed in males of several species that belong to the D. exilis-species group. As shown by SEM images these modifications differ greatly between the species, both at light microscopic and ultrastructural levels. These modifications are introduced as a new set of characters in the identification key. Finally, brochosomes were detected on the midleg of three SEM-examined Drapetis species, documenting indirectly that small leafhoppers are regularly used as prey.